POROUS BORDERS AND INSECURITY: A STUDY OF NIGERIA-NIGER BORDER - Omojowo, Sunday; Adenuga , Asimiyu (Malaysian Journal of International Relations, 2025)
Borders remain a vital component of a nation’s security architecture, serving as both the first line of defence and the final safeguard of territorial integrity. In many developing countries, particularly in Africa, borders are problematic due to their porosity and inadequate demarcation. This paper examines the factors contributing to the porous nature of the Nigeria–Niger border. It employs a desk review research method and draws on structural–functional theory as its analytical framework. It argues that the Nigeria–Niger border is porous not only because of its vast expanse but also due to unprofessional and corrupt practices among border officials, which are consistently exploited by non-state actors such as bandits and terrorists. These vulnerabilities have enabled widespread insecurity affecting both nations. The paper further contends that the porous border has facilitated significant economic sabotage and a breakdown of law and order, posing serious threats to the territorial sovereignty of Nigeria and Niger. The study concludes that the Nigeria–Niger border is inadequately secured, allowing armed non-state actors to operate with impunity and potentially contributing to state fragility. It therefore recommends that both governments invest in advanced technological surveillance tools, including drones and sensors, and address the underlying drivers of crime, such as poverty and unemployment, through robust economic and developmental policies.